Interannual variability of the Madden‐Julian Oscillation and its impact on the North Atlantic Oscillation in the boreal winter. Issue 13 (2nd July 2015) - Lin, Hai; Brunet, Gilbert; Yu, Bin
Abstract Interannual variability of the Madden‐Julian Oscillation (MJO) and its influence on the extratropical teleconnection are analyzed. It is found that there is an interannual shift of the MJO activity between the Indian Ocean and the western central Pacific. This is reflected by the year‐to‐year changes in the occurrence frequency of individual MJO phases. The leading mode of an empirical orthogonal function analysis of occurrence frequency of MJO phases shows an out‐of‐phase relationship between MJO phase 7 and phases 3–5. During winters when the MJO convection occurs more frequently in the Indian Ocean (phases 3–5), a winter mean positive North Atlantic Oscillation (NAO) tends to occur. These results indicate that the seasonal mean convection activity over the Indian Ocean related to the MJO is a possible driving forcing for the seasonal mean NAO variability in the boreal winter.